Impact of mobility models on social structure formation in opportunistic networks - Halikul, Lenando; Mohamad Nazim, Jambli; Kartinah, Zen; Johari, Abdullah (2013)
In mobile opportunistic networks, the network topology is unpredictable and very dynamic due to the existence of the mobile nodes in the network. The nodes’ mobility affect the nodes’ interaction frequency. Hence, it also affecting the social structure formation between nodes. In this paper, we study the impact of different mobility models namely Random Walk, Random Waypoint, Gauss Markov and D-GM on the social structure formation in opportunistic networks. The study shows that different mobility models have different impact on the social structures formation. Based on our experimental results, the Gauss Markov model provides better social structure compared to others because it creates more opportunities for a node to interact with different nodes.